Mineralogy of Hydrothermal Alteration Rocks in Kaligono Region, Kaligesing District, Purworejo Regency, Central Java - setiyawan, Reynaldo; verdiansyah, okki (ReTII, 2021)
ABSTRAK A belt of significant copper-gold mineralization runs through central Java's southern mountains. Kokap, Bagelen, Salaman, and eventually the discovery of porphyry in Sumbersari are all prospective Au-Cu mineralization in Kulonprogo. The research focuses on outcrop observation and laboratory investigation, such as XRD, petrography, and ore microscopy, with the goal of determining the Sumbersari area's mineralogical paragenesis. The research location is located in the Khuluk Gajah part of the old Kulon Progo volcanic complex. The goal of this research is to figure out the mineralogy of the hydrothermally altered rocks in the vicinity. Based on lithology, alteration, and mineralization data gathered from the surface mapping. One of the lithologies obtained is microdiorite, with illite-sericite secondary biotite as the result of megascopic examination of the alteration and Quartz-andesine-albit-serisite-phengitilitklinochlor as the result of XRD analysis. Obtaining crossing veinlets (stockwork) in the forms of "A," "AB"/"B," and "D" veins is also possible. The hydrothermal fluid temperature is in the range of 280 – 320 oC, with a neutral-alkaline pH, based on these mineral correlations (6-7). The Sumbersari sample's hydrothermal alteration reveals a porphyry and epithermal overprint mechanism. Kata kunci : busur magmatik, Porfiri, alterasi hidrotermal, dan XRD